2008
DOI: 10.17221/361-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary selenium sources on growth performance, breast muscle selenium, glutathione peroxidase activity and oxidative stability in broilers

Abstract: This study examined the effects of supplementation of dietary sodium selenite and sodium enriched alga Chlorella on growth performance, selenium concentration in breast meat and excreta, activity of glutathione peroxidase in meat, and oxidative stability of meat in broilers. Sexed broiler cockerels Ross 308 were allotted to 3 dietary treatments, each comprising 100 chickens. The basal diet was supplemented with 0 (control) or 0.3 mg/kg Se from sodium selenite (SS) or Se-Chlorella (SCH). Dietary supplementation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
39
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 20 publications
13
39
1
Order By: Relevance
“…The increase in selenium concentration in breast meat due to dietary selenium supplementation is in agreement with findings presented by Ševčíková et al (2006), Dlouhá et al (2008) and Skřivan et al (2008a). Little information about the effect of SCH and SP on selenium content in breast meat and GSH-Px activity was published.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The increase in selenium concentration in breast meat due to dietary selenium supplementation is in agreement with findings presented by Ševčíková et al (2006), Dlouhá et al (2008) and Skřivan et al (2008a). Little information about the effect of SCH and SP on selenium content in breast meat and GSH-Px activity was published.…”
Section: Discussionsupporting
confidence: 90%
“…Accordingly, Dlouhá et al (2008) or Skřivan et al (2008a) confirmed that organic sources of selenium increased its content in breast meat. The organic form of selenium is deposited to a greater extent than the inorganic form.…”
mentioning
confidence: 68%
See 3 more Smart Citations